KONSEP DASAR PENDIDIKAN ISLAM (Istilah Term Pendidikan Islam dalam al-Qur‟an) - ALI ANAS NASUTION (IAIN Padangsidimpuan, 2014)
In holy Quran, the phrase of Islamic educational is always using someterminologies in term likes al-Tarbiyah, al-Ta‟lim and al-Ta‟dib. These terms have different meaning and different sense, although these terms areused in context of Islamic educational. Based on these terms, the word of al-Tarbiyah is always using, and got the popular place in circle of Islamic educational, so that, the term of Islamic educational use “al-Tarbiyah al-Islamiyah”. Whereas the terms of al-Ta‟lim and al-Ta‟dim are used rarely.Nevertheless, these terms like as al-Tarbiyah, al-Ta‟lim and al-Ta‟dim have the same meaning.